Analisis Produk Deposito Mudharabah dan Penerapannya pada PT BPRS Amanah Ummah - Siti Afifah; Ahmad Sobari; Hilman Hakiem (AL-MUZARA'AH, 2013)
This paper attempts to analise the mudarabah fixed deposits product and its implementation in PT BPRS Amanah Ummah. This paper also tries to analise the nisbah examination on profit and loss sharing.The method used in this study is descriptive method. Fixed deposits account in PT BPRS Amanah Ummah has been known for its transaction using mudaraba contract. The contract, basically, involves two parties which have been working together as an investor (shahibul maal) and entrepreneur (mudharib) throughout the contract period. Bank has its own responsibility as the entrepreneur. The profit and loss are shared between them as stated in the contract and has been agreed by all involved parties.The proportion is indeed appeared as the result of bargaining process prior to the final agreement between them. If any loss occurred, the investor is the one who responsible on it. The entrepreneur is ‘only’ burdened on time and management loss. However, the situation may differ if the loss is caused by human error (the entrepreneur).